Discurso e poder em pesquisas pós-estruturalistas-foucaultianas no GT de currículo da ANPED no período de 2000 a 2005 - NASCIMENTO, Lucineide Soares do (2007)
This dissertation renders the searching about articles approved by the National Association of Post Graduation and Educational Research ANPEd, at the curriculum work group, from 2000 to 2005. Among 76 articles, written in Portuguese and easily found in the Institution site, they selected 14 they considered inserted in the Foucault post structuralist conception. The problem was constructed and delimitated from the following question : How the discourse and power concepts are involved through theory and methodology in the Foucault post structuralist texts, published by ANPEd from 2000 to 2005 ? The objective was getting the answers for these questions :a) What are the methodology strategies used in analysis that deal with the concepts above, from the Foucault used conception ? b) What is the curriculum and research production involved in that theory and method perspective ? c) What are the possible effects in actual curricula discussions ? The methodology was generated from Foucault contributions inside his works and discussions. They are in actual curriculum theories at the National scene. The theory was used as an exercise about discourse problems and construction, concepts and perspectives that build the curriculum and research at the actual curricula theories area. Among the most significant results we can find discussions about the difference of the curriculum inventivo (creative) feature and the post structuralist research as important events ; the post curriculum is possible to happen but it does not happen yet. It does not exist as an effective discourse practice or as an investigation object to post theories ; the post research, on the other hand, happens as knowledge in its acontecência (existance) and shows its effects : the construction of a repeating narrative about some dimensions, functions, and effects of power and discourse about the analysis of different curricula texts ; the existance of interditos in curricula discussions as the exclusion/substitution or shyness in the use of words that can lead to some form of prescription and, the desire for truth and power as discourse effects of post structuralist researches. Observing Foucault orientations, these interditos were analised in their discourse production and positive effects.